Wrestling with democracy : voting systems as politics in the twentieth-century West - Pilon, Dennis, 1965- (Studies in comparative political economy and public policy ;, 2013)
"Though sharing broadly similar processes of economic and political development from the mid-to-late nineteenth century onward, western countries have diverged greatly in their choice of voting systems: most of Europe shifted to proportional voting around the First World War, while Anglo-American countries have stuck with relative majority or majority voting rules. Using a comparative historical approach, Wrestling with Democracy examines why voting systems have (or have not) changed in western industrialized countries over the past century.